Response of Stream Flow peak to Climate Change in Kainji and Shiroro Hydroelectric Power Generations, Niger State, Nigeria (Journal of Geography, Meteorology and Environment, 2025)
Climate changes impact hydrological processes and control stream flow at the basin scale. This study was carried out to examine the potential influence of climate change on stream flow peaks in Kainji and Shiroro Hydropower Projects, Niger State for the period 1967-2017. The study uses long term historical data on rainfall, minimum and maximum air temperature, runoff peak discharge and evapotranspiration to investigate observed hydro-climatic variability and climate change. The Mann–Kendall and Sen’s slope estimator tests were used to detect monotonic trends in the hydro-climatic variables and their magnitude with MAKESENS_1_0 software. The contribution of climate changes to stream flow was revealed by climate elasticity model. The results showed an increasing trend in minimum and mean temperature, rainfall and stream flow while evapotranspiration and maximum temperature showed decreasing trend. Mean annual rainfall and runoff changes in Kainji and Shiroro showed an increasing trend that is statistically insignificant. The precipitation elasticity of stream flow was 1.0 in Shiroro and 0.99 in Kainji indicating that 1 percent change in precipitation caused a corresponding 1 percent increase in runoff and revealed that stream flow increases with increasing precipitation, whereas the evapotranspiration elasticity of stream flow is -0.12191in Kainji indicating that a 1 percent increase in potential evapotranspiration produces 0.122decrease in stream flow and -0.533 for Shiroro indicating a 1 percent increase in evapotranspiration results in 0.5 percent decrease in stream flow Peak due to rainfall events are increasing in both stations.
Keywords: Climate Change, Shiroro Hydropower Station, Kainji Hydropower Station, Mann Kendall test, Climate elasticity and Stream Flow Peak